Frankenstein 200 : the Birth, Life, and Resurrection of Mary Shelley's Monster - Baumann, Rebecca (Indiana University Press, 2018)
Two centuries ago, a teenage genius created a monster that still walks among us. In 1818, Mary Shelley published Frankenstein, and in doing so set forth into the world a scientist and his monster. The daughter of Mary Wollstonecraft, famed women's rights advocate, and William Godwin, radical political thinker and writer, Mary Shelley is considered the mother of the modern genres of horror and science fiction. At its core, however, Shelley's Frankenstein is a contemplation on what it means to be human, what it means to chase perfection, and what it means to fear things suchsuch things as ugliness, loneliness, and rejection. In celebration of the two hundredth anniversary of the publication of Frankenstein, the Lilly Library at Indiana University presents Frankenstein 200: The Birth, Life, and Resurrection of Mary Shelley's Monster. This beautifully illustrated catalog looks closely at Mary Shelley's life and influences, examines the hundreds of reincarnations her book and its characters have enjoyed, and highlights the vast, deep, and eclectic collections of the Lilly Library. This exhibition catalog is a celebration of books, of the monstrousness that exists within us all, and of the genius of Mary Shelley.